STEROIDS IN CARDIAC SURGERY: A SYSTEMATIC REVIEW - Ma’bud, Tasia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Since there has been considerable research on the prophylactic administration of corticosteroids in adult patients undergoing cardiac surgery with cardiopulmonary bypass (CPB), there is limited evidence to suggest that steroid therapy substantially affects patient outcomes.Objective: This study aims to investigate the effects of administering steroids during cardiac surgery.Aim: This study complied with the PRISMA 2020 guidelines for systematic review and meta-analysis. The researchers verified the study's similarity to become feasible. Publications from 2015 to 2023 were searched using online reference databases, including Pubmed and SagePub. Review articles, previously published works, and incomplete articles were dismissed.Methods: The search identified 9,316 articles in PubMed and 7,654 articles in SagePub. In 2015, a search on PubMed identified 238 articles, and a search on SagePub yielded 121 articles. At last, 27 papers were selected, with 15 sourced from PubMed and 12 from SagePub. We included five studies that met the criteria.Conclusion: The relationship between prescribing steroids and surgical site infections is still debated. Corticosteroid therapy has been found to reduce the incidence of postoperative delirium.